Local peer influence on dividend payout decisions - Cave, Joshua; Lancheros, Sandra (Journal of Banking & Finance, 2024)
Using a large sample of US-listed firms, we examine how firms’ dividend payout decisions are influenced by the dividend policies of their local peers. We find that the decisions to increase and decrease dividends are both influenced by the payout choices of firms headquartered in the same locality. We show that local peer effects are driven by the desire to compete for local dividend clineteles, with local peer effects proving more pronounced in geographies with greater retail investors clienteles, institutional-tax clienteles, and agency-cost clienteles. In contrast to dividends, share repurchases are not influenced by local peer repurchase decisions. Our findings prove robust to various sampling methods, peer portfolios, model specifications, and estimation techniques.